IMPLEMENTASI TEKNOLOGI TRUE SHALLOT SEED (TSS) PADA PETANI BAWANG MERAH (Allium cepa L.) DI KECAMATAN CILAWU KABUPATEN GARUT - Lucky Novianti; Harniati Harniati; Dedy Kusnadi (Sekolah Tinggi Pariwisata Mataram, 2020)
True Shallot Seed (TSS) technology is one of the latest innovations in onion cultivation which is considered effective in reducing production costs and increasing onion productivity. This study aims to analyze the level of implementation of farmers in implementing TSS technology and analyze the factors that influence the level of implementation of farmers in applying TSS technology, as well as formulating strategies to improve the implementation of farmers in the application of TSS technology in onion cultivation. This research has been carried out in the village of Mekarmukti, District of Cilawu, Garut Regency in March to June 2020. The sample in this study was 35 shallot farmers who were members of the farmers' group. The sample is determined using the saturation sampling method. Research variables consisted of farmer characteristics, external characteristics, innovation characteristics and implementation. Data collection is done by distributing questionnaires, interviews and observations. Data were processed using descriptive statistical analysis techniques and multiple linear regression. The results of research on the implementation of TSS technology in onion farmers are in the medium category. Factors affecting the level of technological implementation are the availability of facilities, the availability of infrastructure, the relative benefits and triability. The strategy used to improve technology implementation among farmers is carried out by conducting extension activities and training farmers about TSS technology so that the possibility of technology can be tried and applied.